Gaps in the use of the Internet: A front of action far behind in Colombia - Martínez-Coral, Patricia Eugenia (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
This article presents the results of an exploratory research, through which the scope of investment projects executed by the Universal Service Fund, during the last eight years to promote access and use of the Internet in households with low socioeconomic strata, was analyzed. Elements such as coverage, service offerings, selection of beneficiaries and executors, design of applied subsidies, and amount of investment, served as guiding criteria in the development of the analysis, and they were complemented by the reconstruction of the sectoral context in which each project has been implemented. The study of the universal service policy in Colombia allows to conclude that there is a significant gap in the dimensions of use that must accompany the supply of infrastructure. Although the subsidized deployment of last-mile networks, and the establishment of maximum broadband service tariffs, aim to overcome affordability barriers that hinder technological diffusion, it turns out to be imperative to develop strategies that increase the promise of value of Internet use, in such a way that the beneficiaries not only reward the public investment by their willingness to pay for the service, strengthening the sustainability of these types of projects, but also taking advantage of the conditions of access, by making productive use of the network.